Seasonal and Spatial Variations in Synechococcus Abundance and Diversity Throughout the Gullmar Fjord, Swedish Skagerrak - Christien P. Laber; Benjamin Pontiller; Benjamin Pontiller; Carina Bunse; Carina Bunse; Carina Bunse; Christofer M. G. Osbeck; Clara Pérez-Martínez; Danilo Di Leo; Daniel Lundin; Catherine Legrand; Catherine Legrand; et al. (Frontiers in Microbiology, 2022)
The picophytoplankton Synechococcus is a globally abundant autotroph that contributes significantly to primary production in the oceans and coastal areas. These cyanobacteria constitute a diverse genus of organisms that have developed independent niche spaces throughout aquatic environments. Here, we use the 16S V3–V4 rRNA gene region and flow cytometry to explore the diversity of Synechococcus within the picophytoplankton community in the Gullmar Fjord, on the west coast of Sweden. We conducted a station-based 1-year time series and two transect studies of the fjord. Our analysis revealed that within the large number of Synechococcus amplicon sequence variants (ASVs; 239 in total), prevalent ASVs phylogenetically clustered with clade representatives in both marine subcluster 5.1 and 5.2. The near-surface composition of ASVs shifted from spring to summer, when a 5.1 subcluster dominated community developed along with elevated Synechococcus abundances up to 9.3 × 104 cells ml–1. This seasonal dominance by subcluster 5.1 was observed over the length of the fjord (25 km), where shifts in community composition were associated with increasing depth. Unexpectedly, the community shift was not associated with changes in salinity. Synechococcus abundance dynamics also differed from that of the photosynthetic picoeukaryote community. These results highlight how seasonal variations in environmental conditions influence the dynamics of Synechococcus clades in a high latitude threshold fjord.